INTEGRASI NILAI KARAKTER MELALUI DESAIN BAHAN AJAR BAHASA INGGRIS UNTUK USIA DINI - Novitasari, Lusy; Wulandari, Rifa Suci (Universitas Islam Balitar, 2021)
Learning English in addition to developing cognitive abilities but also instilling character values in students. Good learning is also supported by the design of teaching materials that suit the needs of students. The purpose of this study was to describe the design of English teaching materials for early childhood as a means of inculcating character values. This study uses a qualitative descriptive research design. The analysis technique used is content analysis. The results of the study indicate that the character values that can be developed through the design of English teaching materials for early childhood are religious, friendly/communicative curiosity, hard work, love of reading, and responsibility.